EFFECT OF WATER STRESS ON YIELD AND YIELD COMPONENTS OF BREAD WHEAT GENOTYPES. - & Kadhem, Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A field experiment was conducted during 2014 -2015 and 2015-2016 seasons at the  Field Crops Research Station Abu Ghraib, to study the effect of water stress, on yield and yield components of  bread wheat genotypes .The water stress treatment were 25% (S1) and 75% (S2) depletion of soil available water . The experiments was conucted using a split plot with in arrangement Randomized Complete Block Design with three replications. Water stress treatments were assigned to the main-plot, while, 27 wheat genotypes  were assigned to sub-plots. The results indicated that water stress treatment (S2)  significantly decreased  the number of spikes m-2,  number of grain.spike-1, 1000 grain weight and grain yield. The genotypes showed a differences in all characters studied. The genotype 26 produced the highest number of spikes m-2(355.8) and did not significantly differ from Bohooth10 347.2 spike.m-2.The Bohooth10 gave highest in the number of grain spike-1 (62.07) . The genotype 25 produced the highest weight of 1000 grains (40.05,37.09 gm)The genotype 26 produced highest grain yield (6.117 and 5.074 ton h-1 ) for two seasons, respectively but differed significantly from IPA99 which gave lowest  grains yield ( 3.395 and 3.020 Tun.h-1) for two seasons respectively.